Look at this proof

let x = 1 , $x^2$ =1 , $x^2=x$ -----------------------------(1)

then $x^2-1=x-1$ , $(x-1)(x+1)=x-1$ -----------------(2)

so , $x+1 = 1$ , which is equal to 2=1 Q.E.D---------(3)

Where did the "proof" get wrong ?

1
math is magical
2
3

**
This section requires Javascript.
**

You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.

If $x=1$ then $x-1=0$ .In (3) you are assuming the result of dividing both sides by $x-1\rightarrow 0$ as one which not allowed so answer is $\boxed{(3)}$